(untitled) (Jurnal Teknologi (Sciences & Engineering), 2016)
Lightning is a natural phenomenon that cannot be prevented, therefore the specific system need to be installed in the building to reduce or eliminate the impact of lightning flash and safely discharge to the ground. The country along the equator including Africa, South America and Southern Asia received the highest number of lightning. Malaysia experienced in average of 100 to 140 days of lightning and 600000 to 1300000 number of lightning flash per year. This research is conducted to identify the materials selection for the lightning protection system especially the down conductor cable. Several projects around Malaysia had been selected for this purpose. From the research, they are two types of lightning protection system commonly implemented in Malaysian buildings; the conventional method and structural bonding method. It was found that 23 % of the projects used structural bonding method, mostly from the government projects, and 77% of the projects used conventional method. For the down conductor cable selection, the conventional method used the copper and aluminium tape. And for the structural bonding method the galvanized steel iron was used as the down conductor cable.